Recycling of aluminum alloy from Al-Cu metal matrix composite reinforced with SiC particulates - Sharma, Ashutosh; Ahn, Byungmin (Korean Journal of Materials Research, 2018)
In this study, we investigate the recycling of aluminum-based metal matrix composites(AMCs) embedded with SiC particulates. The microstructure of the AMCs is characterized by X-ray diffraction and scanning electron microscopy. The possibility of recycling the composite scrap is attempted from the melted alloy and SiC particulates by re-melting, holding and solidification in crucibles. The recovery percentage of the matrix alloy is calculated after a number of holding times, 0, 5, 10, 15, 20, 25 and 30 minutes and for different particulate sizes and weight fractions in the Al matrix. The results show that the recovery percentage of the matrix alloy, as well as the time required for maximum recovery of the matrix, is dependent on the size and weight fraction of SiC particulates. In addition, the percentage recovery increases with particulate size but drops with the particulate fraction in the matrix. The time to reach maximum recovery falls rapidly with an increase in particulate size and fraction.
Keywords: Aluminum based metal matrix composites; Automotive; Holding time; Particulate; Particulate fraction; Percentage recovery; Recovery percentages; Weight fractions; Aluminum; Automotive; Composite; Holding time; Particulate; Recycling